Enhancing Slow Learners' Understanding of Human Movement System Through Contextualized Animation Media - Riyanto, Subur; Suparno, Suparno (Papanda Publisher, 2025)
Slow learners face significant challenges in understanding abstract scientific concepts, particularly the human movement system, necessitating innovative pedagogical approaches. This study investigated the effectiveness of contextualized animation media in enhancing slow learners' comprehension of the human movement system in sixth-grade elementary education. Employing classroom action research following the Kemmis and McTaggart model, this study involved 17 sixth-grade students, including five identified slow learners, over two months across two cycles. Data were collected through pre-tests, post-tests, observation sheets, attitude assessments, and semi-structured interviews. The intervention utilized contextualized animation with adjustable playback speeds, interactive features, and real-life movement examples. Mean cognitive scores increased 35.59 points from baseline (47.06) to post-intervention (82.65), with 88.24% achieving mastery (≥70). Slow learners demonstrated remarkable progress, with mean scores rising 39.5 points to 72.5, and 80% meeting mastery criteria. Significant improvements were observed across affective (+22.20 points) and psychomotor (+23.33 points) domains, with student participation increasing from 65.20% to 79.62%. Contextualized animation media effectively enhances slow learners' understanding of complex scientific concepts when designed with learner-controlled features, content segmentation, and contextual examples, supporting inclusive science education in mainstream classrooms.